Solutions for Managing Tomato Culls in Florida Tomato Packinghouses - Gurpal Toor; Maninder Chahal; Bielinski Santos (EDIS)
Florida is the single largest producer of fresh-market tomatoes in the United States. Driven by urbanization and generation of large amounts of tomato culls, tomato packers in Florida often struggle to find ways to dispose of culls generated during the cleaning and sanitizing of tomatoes. This 5-page fact sheet provides guidelines for appropriate management practices to increase the use of culls produced in tomato packinghouses in Florida. Written by Gurpal Toor, Maninder Chahal, and Bielinski Santos, and published by the UF Department of Soil and Water Science, September 2012.